Evaluation of the Implementation of the Discovery Learning Model by Utilizing M-Edukasi - Manikowati Manikowati (Teknodika, 2021)
Implementing the best learning during the COVID-19 pandemic is challenging. Also, applying a learning model integrated with ICT is urgently required. It leads to applying discovery learning using mobile learning, hereinafter referred to as M-Edukasi. This research aimed to evaluate the strengths and the weaknesses of the model using M-Edukasi to provide recommendations for the stakeholders, in this case, teachers, school principals, and the Center for Multimedia Education and Culture Development (BPMPK), for further improvements. To obtain the data, the applied research methodology was descriptive qualitative. The instruments used were document notes, observation sheets, and interview guidance. The results showed that three learning processes, namely planning, implementing, and assessing, were interconnected and influential. Better processes in the preceding step would make the later ones better and vice versa. Meanwhile, the weaknesses were apparently influenced by vague and unspecific statements in the lesson plan (RPP). Moreover, there was the less optimal use of M-Edukasi. There was no usage manual completed the medium. Those weaknesses, then, affected the students’ learning outcomes that were less than optimal.